Modifiable risk factors for peritoneal dialysis-related infections - a population-based cohort study on risk factors and outcomes in South Sweden - Ljungquist, Oskar; Tobijaszewska, Marta; Torisson, Gustav; Martus, Giedre; Segelmark, Mårten; Tverring, Jonas (Frontiers in Nephrology, 2025)
BackgroundThe risk of infection-related death is high in patients undergoing dialysis. This study aimed to identify the modifiable risk factors for PD-related infections in patients undergoing peritoneal dialysis.MethodsThis was a population-based retrospective cohort study conducted in Skåne, South Sweden, which included all patients receiving peritoneal dialysis (PD) between 2011 and 2020. The primary outcome was PD-related peritonitis, and the secondary outcome was a composite of PD-related infections, that is, peritonitis, exit site, or tunnel infections. Time-to-event frailty models, unadjusted and adjusted for age at PD start, sex and Charleson comorbidity index, were used to investigate potentially modifiable risk factors for PD-related infections. Cox regression models were subsequently used to analyze the relationship between PD-related infection episodes and all-cause mortality during the study period.ResultsIn total, 545 patients were included in the study, of whom 212 (39%) patients had at least one episode of peritonitis during a median follow-up time of 1.6 years. We found that BMI ≥ 30 may be associated with a clinically relevant increased risk for PD-related infection (aHR 1.45, 95% CI 1.08-1.93, p-value 0.012, nevents = 486), but not for peritonitis alone (adjusted Hazard Ratio, aHR, 1.34, 95% CI 0.95- 1.91; p = 0.099; nevents = 365). Patients with >3 peritonitis episodes had an almost three-fold increased risk of all-cause mortality (aHR, 2.66; 95% CI 1.56-4.52, p < 0.001).ConclusionWe found that a BMI ≥ 30 may be a modifiable risk factor for peritoneal dialysis-related infections and that multiple episodes of infectious complications of peritoneal dialysis are associated with increased all-cause mortality.